2009
DOI: 10.1111/igc.0b013e3181a19eca
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hepatocyte Nuclear Factor-1β in the Pathogenesis of Clear Cell Carcinoma of the Ovary

Abstract: This review summarizes recent advances in the HNF-1beta and its target genes; the potential challenges to the understanding of carcinogenesis, pathogenesis, and pathophysiology of CCC; and a possible novel model is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
78
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 118 publications
0
78
0
Order By: Relevance
“…Clarification of the mechanism of these metabolic characteristics may yield a new strategy to overcome the disease. Several studies have considered the mechanism of facilitated glycogen accumulation of OCCC (12,13), but a conclusion has not yet been reached. Some studies have found that the glycogen accumulation in several kinds of tumor cells was accelerated under hypoxic conditions (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Clarification of the mechanism of these metabolic characteristics may yield a new strategy to overcome the disease. Several studies have considered the mechanism of facilitated glycogen accumulation of OCCC (12,13), but a conclusion has not yet been reached. Some studies have found that the glycogen accumulation in several kinds of tumor cells was accelerated under hypoxic conditions (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian clear cell carcinoma is diagnosed at an early stage in B60% of patients; however, it carries a worse prognosis because resistance to conventional cytotoxic chemotherapeutic agents is common even with early disease. [5][6][7] Identification of the molecular pathways, which confer chemoresistance in ovarian clear cell carcinoma is essential for the development of novel targeted therapeutic agents.…”
mentioning
confidence: 99%
“…This suggests biological differences between clear cell carcinomas that arise in association with adenofibroma vs. endometriosis. Recent genome-wide expression analyses have demonstrated the specific expression of hepatocyte nuclear factor (HNF)-1β in endometriosis and clear cell carcinoma, but not endometrioid adenocarcinoma, suggesting that early differentiation into the clear cell lineage occurs in the endometriosis with HNF-1β overexpression (32). The HNF-1β-dependent pathway provides new insights into the regulation of apoptosis, the cell cycle, glycogen synthesis and chemoresistance (32).…”
Section: Clear Cell Carcinoma Of the Ovarymentioning
confidence: 99%
“…Recent genome-wide expression analyses have demonstrated the specific expression of hepatocyte nuclear factor (HNF)-1β in endometriosis and clear cell carcinoma, but not endometrioid adenocarcinoma, suggesting that early differentiation into the clear cell lineage occurs in the endometriosis with HNF-1β overexpression (32). The HNF-1β-dependent pathway provides new insights into the regulation of apoptosis, the cell cycle, glycogen synthesis and chemoresistance (32). It has been reported that HNF-1β gene might play a role in carcinogenesis, pathogenesis, and the pathophysiology of clear cell carcinoma of the ovary (32).…”
Section: Clear Cell Carcinoma Of the Ovarymentioning
confidence: 99%